UV–vis light responsive Bi2WO6 nanosheet/TiO2 nanobelt heterojunction photo-catalyst for CO2 reduction - Maryam Ahmadi; Seyed Mehdi Alavi; Afsanehsadat Larimi (Catalysis Communications, 2023)
A series of Bi2WO6/TiO2 composite photocatalysts with different ratios of Bi2WO6 nanosheets to TiO2 nanobelts (1, ½, ⅓ and ¼) were synthesized by hydrothermal method and evaluated for CO2 photoreduction. The structural and optical properties of these photocatalysts were investigated by XRD, N2-physisorption, EDX, FESEM, Raman, TPD, DRS and PL. Bi2WO6/TiO₂ composite photocatalysts show enhanced CO2 adsorption capacity and coversion performance compared to both pure TiO₂ and bulk Bi2WO6. Loading Bi2WO6 nanosheets on TiO2 nanobelts leads to formation a heterojunction, which enhances the photocatalytic visible light performance by decreasing the recombination rate of photoinduced electron-hole pairs. The maximum CH4 production of 18.95 μmol/gcat in 8 h has been reported for composite with Bi2WO6/TiO₂ ratio of ½, which is 3 times higher than that of bulk Bi2WO6 and pure TiO2.